Lewis Acid Catalyzed Divergent Reaction of Bicyclo[1.1.0]Butanes With Quinones for the Synthesis of Diverse Polycyclic Molecules - Hu, Qian‐Qian; Geng, Ze‐Xiang; Bai, Xue; Chen, Jie; Zhou, Ling (Angewandte Chemie International Edition, 2025)
Bicyclo[1.1.0]butanes (BCBs) are highly strained hydrocarbons with unique structural properties and intrinsic reactivity, making them valuable building blocks for constructing complex molecular architectures. Herein, we report the Lewis acid‐catalyzed divergent reactions of BCBs with quinones, yielding a diverse array of polycyclic molecules. Using Sc(OTf)₃ as a catalyst, pyrazole‐substituted BCBs efficiently undergo formal (3 + 2) cycloaddition reactions with quinones, producing highly substituted bicyclo[2.1.1]hexanes featuring a caged framework. Monosubstituted BCB ketones undergo a sequential cascade involving Alder‐ene reaction, 4π electrocyclic ring‐opening, and [4 + 2] cycloaddition reaction, yielding fused benzoxepines efficiently. Disubstituted BCB esters, ketones, and amides undergo a tandem isomerization and (3 + 2) cycloaddition process, stereoselectively yielding tetrahydrocyclobuta[b]benzofuran products. Notably, strong Lewis acids such as SnCl₄ and BiBr₃ directly participate in the ring‐opening reactions of monosubstituted BCB ketones, generating halogenated cyclobutane derivatives. Additionally, the synthetic potential of these approaches has been further highlighted through scale‐up experiments and a range of transformations. This study demonstrates the tunability of reaction pathways based on the diverse substitution patterns of BCBs, providing efficient methods for the synthesis of a range of polycyclic compounds. Lewis acid‐catalyzed reactions between bicyclo[1.1.0]butanes (BCBs) and quinones yield diverse polycyclic molecules. Specifically, pyrazole‐substituted BCBs afford bicyclo[2.1.1]hexanes, monosubstituted variants undergo cascade transformations to benzoxepines, disubstituted BCBs enable the stereoselective assembly of tetrahydrocyclobuta[b]benzofurans, while strong Lewis acids induce the formation of halogenated cyclobutane derivatives through a ring‐opening reaction.